Midazolam versus Neostigmineadding to Lidocaine in Post Operation Pain in Colporrhaphy Surgery in Spinal Anesthesia - Alireza Kamali; Maryam Shokrpour; Khatereh Vatanpour; Majid Eraghi (Tehran University of Medical Sciences, 2012)
Objective: To compare the effect of intrathecal midazolam versus neostigmine added to lidocaine on the duration of sensory block and the duration of postoperative pain relief in women undergoing colporaphy in spinal anesthesia. Materials and methods: In this double blind clinical trial we evaluated 60women (ASA) I,II that were candidate to elective colporaphy. The patients were randomly divided in three groups ,first group(midazolam group)received hyperbaric lidocaine and 1mg midazolam(0.5cc),second group ( neostigmine group) received hyperbaric lidocaine  and 50µg midazolam(0.5cc) and third group were considered as control and received hyperbaric lidocaine plus normal saline(0.5cc).VAS  pain score 4,12 and 24 hours after surgery and duration of  analgesia in tree groups were compared. Results: The duration of sensory block in the midazolam group was 98.4±18.2minuts, 74.5±32.6 in neostigmine and 64.5±9.9 in control group and difference between three groups was significant (p=0.001). Postoperative pain scores in midazolam group was 1.5±1.3, in neostigmine group was 2.4±1.6 and in control group was 3.5±2.7 and difference between three groups was significant (P=0.009). Conclusion: Midazolam & neostigmine added to lidocaine 5% prolonged postoperative analgesia in colporrhaphy surgery in spinal anesthesia but midazolam was more effective than neostigmine.